The concept of risk – a threat and opportunity - Rak, Janusz; Żywiec, Jakub (Instal, 2020)
Risk is associated with an action whose effect can be quantified using a measure of probability and effects. The paper proposes a new approach to risk, using threats and opportunities. The Bow Tie method has been proposed for threat and opportunity analysis. Strategies for responding to risks related to threats and opportunities were indicated. The subject of the work refers to current risk management standards. Threats increase risk and opportunities reduce it. The relationship between opportunities and threats can be determined by the risk difference. A modified risk formula was presented and a new matrix was developed based on it. To show the advantages of the method an application example is shown. The final fragment of the thesis concerns surveys on the perception of threat and opportunity in a water supply company and its external environment. The content of the work confirms the well-known paradigm that missed opportunities become threats.
Keywords: risk; risk management; threats; opportunities